Cultural accessible pedestrian ways. The case of Faro historic centre - Pires Rosa, Manuela (2020)
In a historic city the existence of accessible pedestrian routes constitutes an essential feature to a true access to culture heritage, contributing for processes of social inclusion. It is necessary to create accessible pedestrian infrastructures network to hold a set of attributes that guarantee usability for all citizens. The creation and design of an accessible physical environment should be considered as a criterion of urban quality, which will make walking more pleasant not only for the elderly and people with disabilities but, also, for the entire resident population and tourists. In this case study it is ascertainable whether the physical characteristics of pedestrian infrastructures of cultural interest, located in the Historical Centre of Faro (Portugal), comply with the requirements of the National Law of Accessibility. There has, therefore, been created a methodology for evaluating the accessibility of pedestrian infrastructure through the construction of performance indicators. The analysis is achieved through a model of evaluation of the degree of conformity of the spaces, and presented, spatially, with appeal to a Geographical Information System, which is a tool to support the decision taking in the processes of urban rehabilitation, thus contributing to the choice of priority areas of intervention in the field of accessibility. The diagnosis confirms the existence of inaccessible pedestrian infrastructure and concludes the need to trigger processes of urban renovation.